Exportações brasileiras de soja para os principais destinos: uma análise de persistência à choques - Lima, Juan Lucas Alves de (2022)
Agribusiness is one of the most important sectors in Brazil. Almost a third of the Gross Domestic Product comes from the segment. In 2020, the participation of agribusiness corresponded to about 27% of the National GDP. Currently, soy is the main Brazilian agribusiness product, which is why the country stands out for being a leader in world production and export. This form of production is present in the five corners of Brazil, in nineteen states and the Federal District. In addition to strong production, Brazilian soy is present in a huge range of destinations, reaching 116 countries that buy Brazilian soy. Given the significant importance that soybeans have for Brazil, and for one of the main players in the global scenario, the objective of this study is to analyze whether the series of Brazilian exports to the main destinations have a long memory, that is, if there is persistence to shocks exogenous. The method used to identify the presence of long memory of the export series is the calculation of the Hurst exponent, H, and structural break tests. The exponent is found by calculating the R/S statistic and the DFA method, and the LM structural break test. The results showed that the Brazilian soybean export market is consolidated and that the shocks do not affect exports in a persistent and permanent way.